The shack : a novel - Young, William P.; Jacobsen, Wayne; Cummings, Brad. (Los Angeles : Windblown Media, 2007)
Four years after his daughter is abducted and evidence of her murder is found in an abandoned shack, Mackenzie Allen Philips returns to the shack in response to a note claiming to be from God, and has a life-changing experience.
Keywords: Life change events -- Fiction; Missing children -- Fiction; Oregon -- Fiction; Religious fiction; Suspense fiction